Embracing positivity in dementia caregiving : Links between behavioral symptoms and caregiver well‐being in Malaysia - Mohammed Rasheedan, Ellin; Dayang Zuraina, Abang Haji Kashim; Vimala, Ramoo; Nor Aziyan, Yahaya; Tan, Maw Pin (John Wiley & Sons, Inc, 2025)
Aim: This study investigates the relationships among behavioral and psychological symptoms of dementia (BPSDs), positive aspects of caregiving (PACs), and the psychological well‐being of caregivers for individuals with dementia in Kuala Lumpur, Malaysia. Methods: A total of 178 dementia caregivers were recruited through convenience sampling from a teaching hospital and a private dementia care center. The study utilized three standardized instruments: the Neuropsychiatric Inventory Questionnaire(NPI‐Q) to assess BPSDs as perceived by caregivers, the PAC Scale to measure caregivers' positive perceptions and sense of purpose, and the Scale of Psychological Well‐Being (SPWB).Results: Results indicated that nearly all patients with dementia (PWDs) exhibited at least one type of BPSD, with apathy/indifference being the most prevalent (82.0%),followed by nighttime behavioral disturbances and appetite/eating disturbances(66.3%). The findings revealed that 51.1% of caregivers scored high on PACs, suggesting a substantial sense of purpose in caregiving. In terms of psychological well‐being, 65.2% of caregivers reported high scores, indicating a positive state of mental health. Furthermore, caregiver age showed a significant negative correlation with PAC scores (r = −0.186, p = 0.013), while the number of dependents was positively correlated with PAC scores (r = 0.187, p = 0.012). Additionally, caregiver race was significantly associated with PAC scores. Conclusion: These results highlight the importance of fostering positive caregiving experiences to enhance caregiver well‐being amidst the challenges posed by BPSDs in dementia care.